Comparing the Diagnostic Accuracy of Two Different Resolutions of Radiographs Captured with PSP Digital Intraoral Receptors in Detection of Secondary Caries (In Vitro) - S Mehralizade; S Nemati Anaraki; S Sakhdari; S Miraba; M Amiri Siavashani; S Bayat (Islamic Azad University, 2016)
Background and Aim: Considering the importance of detection of secondary caries, the adverse consequences of false positive and false negative diagnoses and the gap of information in the diagnostic efficacy of digital sensors in detection of secondary caries, this in vitro study sought to compare the diagnostic efficacy of two different resolutions of radiographs obtained by photostimulable phosphor (PSP) plate intraoral sensors in detection of secondary caries in class II composite resin restorations using a standard technique.  Methods and Materials: This diagnostic study was conducted on 40 extracted human second premolars. A classic class II cavity was prepared on one proximal surface of each tooth and restored with composite resin. Intraoral digital radiographs were obtained and saved in High and Super resolutions. Secondary caries were artificially created using a round bur mounted on a high-speed handpiece, and the teeth were radiographed again. Radiographs were saved with the mentioned two resolutions. All the radiographs were evaluated by three observers. Caries detection was classified using the yes/no dichotomous scale and data were statistically analyzed using kappa coefficient.  Results: No significant differences were found in sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of the two resolutions in caries detection (P>0.05). Conclusion: The High and Super resolutions of radiographs taken with digital intraoral PSP plates showed no significant differences in detection of artificially created secondary caries.